Breakthroughs in CH4 capture technologies: Key to reducing fugitive methane emissions in the energy sector - Wenkang Deng; Xiaofeng Xie; Yalou Guo; Guoping Hu (Carbon Capture Science & Technology)
A series of negative impacts caused by greenhouse gas emissions have driven mankind to look for a more efficient and economical strategy to reduce emissions. Methane is the second most abundant anthropogenic greenhouse gas, and implementing cost-effective technologies to reduce its emissions is a crucial pathway toward achieving the milestones outlined in the Paris Agreement. The energy sector has a greater potential for methane emission reductions than other sectors, such as (agriculture and waste) with 75 % reductions achievable by 2050 using existing technologies. Capturing and utilizing fugitive methane from the energy sector could offset the cost of emission reductions to some extent. We analyzed existing methane abatement technologies such as leak detection and repair, flaring, technology standards, and methane capture technologies and found that there are well-established solutions for methane leakage at medium and high concentrations. However, capturing methane from low-concentration sources to meet transportation or utilization requirements remains a significant technical challenge, highlighting the need for advances in low-grade methane enrichment technologies. Adsorption technology has been regarded as a promising methodology for methane capture in recent decades due to various advantages such as high flexibility, low capital investment and energy consumption, and a well-established technological framework. This review provides an overview of recent methane emission trends and prevalent methane abatement strategies, offering a brief analysis of the merits and drawbacks associated with existing methane capture technologies for industrial applications. We analyze the current methane emission reduction policies from major economies and identify a gap between proposed policies and practical actions, suggesting that constructing methane detection systems and developing low-concentration methane capture technologies is a key approach to closing the gap.